Analisis Penerapan PSAK No. 18 (Revisi 2010) Mengenai Akuntansi Dana Pensiun pada Laporan Keuangan Dana Pensiun INTI - Khairina Tamimi Pranotoputeri; Sulistia Suwondo (Indonesian Accounting Literacy Journal, 2023)
A pension fund is a legal entity that becomes an alternative in providing benefits to employees in order to minimize the risks that can be faced in the future. This study aims to analyze the suitability of the application of Pension Fund Accounting with PSAK No. 18, knowing whether or not there are deviations from the accounting treatment applied, and knowing the quality of funding at the INTI Pension Fund. The type of research used is descriptive qualitative research, the data that has been collected is analyzed by describing and comparing the accounting treatment of the INTI Pension Fund with PSAK No. 18. The results of the research based on the Net Assets Report, the Report on Changes in Net Assets, and the Notes to the Financial Statements for 2019 and 2020 show that the accounting treatment applied by the INTI Pension Fund as a whole is in accordance with PSAK No. 18 and there are no deviations, but the quality of INTI Pension Fund funding is at level III, which means the funding wealth is less than solvency obligations.